2018
DOI: 10.3390/ijms19020444
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Differences between Silver Ions and Silver in Nanoforms as Antibacterial Agents

Abstract: Silver is considered as antibacterial agent with well-known mode of action and bacterial resistance against it is well described. The development of nanotechnology provided different methods for the modification of the chemical and physical structure of silver, which may increase its antibacterial potential. The physico-chemical properties of silver nanoparticles and their interaction with living cells differs substantially from those of silver ions. Moreover, the variety of the forms and characteristics of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
290
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(311 citation statements)
references
References 84 publications
(185 reference statements)
2
290
0
2
Order By: Relevance
“…However, most Ag + released from the NPs will not remain freely dissolved in the cell culture medium, due to the high ionic strength of cell culture media and presence of halides (0.12 M total dissolved Cl [66]), amino acids and proteins. Unbound Ag + will precipitate as AgCl and Ag 2 S [62,65] or bind to proteins due to high affinity to thiol groups (SH-groups) [67]. Precipitation was observed when preparing AgNO 3 , and a substantial part of the AgNO 3 solution was most likely precipitated AgCl (K SP 1.77 × 10 −10 M 2 [68]) and not freely dissolved Ag + ions [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…However, most Ag + released from the NPs will not remain freely dissolved in the cell culture medium, due to the high ionic strength of cell culture media and presence of halides (0.12 M total dissolved Cl [66]), amino acids and proteins. Unbound Ag + will precipitate as AgCl and Ag 2 S [62,65] or bind to proteins due to high affinity to thiol groups (SH-groups) [67]. Precipitation was observed when preparing AgNO 3 , and a substantial part of the AgNO 3 solution was most likely precipitated AgCl (K SP 1.77 × 10 −10 M 2 [68]) and not freely dissolved Ag + ions [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is no previous report using the silver nanoparticles formulation Argovit™ for a wound dressings system prepared with a composite electrospun microfiber. However, this AgNP formulation has been effective in the rapid healing of diabetic wounds [107][108][109]. Several authors propose that AgNPs' mechanism of action based on the release of silver ions.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles have become popular as a drug delivery system since they improve bioavailability by enhancing solubility, stability, and biodistribution [88]. Nanoparticles have been used to deliver metals including silver [51,85,[89][90][91], gold [92], copper [93][94][95], and zinc [96]. These metal nanoparticles in the context of urinary catheters will be discussed below.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Additionally, to their toxicity to the host, silver ions irreversibly bind to proteins or molecules, decreasing their antimicrobial activity [89]. However, despite their shortfalls, silver has been incorporated into nanoparticles to overcome some of the negative effects and shown almost identical mechanisms of action [89,90]. Roe and collaborators showed that silver nanoparticles-coated plastic catheters reduce biofilm formation and growth of several pathogens including E. coli, Enterococcus spp.…”
Section: Nanoparticlesmentioning
confidence: 99%